2003
DOI: 10.1023/a:1023030605390
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study examined whether symptoms of depression and concomitant anxiety differed between older and younger medical outpatients referred to a behavioral medicine clinic. In a sample of 178 male veterans aged 21-83 years, older adults (> or = 60 years) reported lower overall depressive symptoms on the Beck Depression Inventory (BDI) and anxiety symptoms on the State-Trait Anxiety Inventory than did younger adults ( < 60 years). Depressive symptoms were highly prevalent. Among older adults, 60.0% scored 10 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…In previous studies, Veterans reported nearly twice the rate of depression symptoms as individuals in the general population (Goldberg et al , 2003; Kazis et al , 1998); however, Veterans in our study were from the general community whereas those in prior studies were recruited from the VA Health Care System (VAHCS). Veterans with more severe disabilities, lower incomes and those without private insurance may be more likely to use the VAHCS (Shen et al , 2008).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In previous studies, Veterans reported nearly twice the rate of depression symptoms as individuals in the general population (Goldberg et al , 2003; Kazis et al , 1998); however, Veterans in our study were from the general community whereas those in prior studies were recruited from the VA Health Care System (VAHCS). Veterans with more severe disabilities, lower incomes and those without private insurance may be more likely to use the VAHCS (Shen et al , 2008).…”
Section: Discussionmentioning
confidence: 85%
“…Twenty-eight percent of Veterans Affairs (VA) outpatients 22 to 90 years of age screened positive for depression (Kazis et al , 1998). Further, as many as 33.8% of Veterans ages 60 and older in a VA behavioral medicine clinic reported elevated depression symptoms (Goldberg et al , 2003). Although post-traumatic stress disorder (PTSD) has been well documented in many Veteran cohorts, no published studies have documented elevated anxiety symptoms that are not specific to PTSD in older Veterans.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Goldberg et al [60] depressive symptoms were highly prevalent and they indicated major depressive disorders. In our study, sex was not significantly related to BDI point values.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should investigate such a curvilinear relationship, as has been found in depression studies with otherwise healthy populations as well as those experiencing unanticipated health-related events (Carlson, 2011; Mirowsky & Kim, 2004; Tuohy et al, 2005). Studies should also examine more closely the types of depressive symptoms (i.e., cognitive, affective, somatic) experienced by stroke survivors across the lifespan, as research suggests that the nature of symptoms may vary by age (Goldberg et al, 2003). …”
Section: Discussionmentioning
confidence: 99%